Association between thyroid hormone levels in early pregnancy and hypertensive disorder of pregnancy - ZHAO Rong，ZHANG Tongqing，ZHANG Yawei，ZHENG Yuanyuan，JIANG Haili (Zhongguo linchuang yanjiu)
Objective To evaluate the relationship between thyroid hormone levels in early pregnancy and hypertensive disorders of pregnancy（HDP），and to provide a reference for clinical prevention of HDP. Methods A total of 2 602singleton pregnant women who were registered and received regular prenatal examinations until delivery at Beijing Obstetrics and Gynecology Hospital，Capital Medical University from June 2020 to February 2023 were retrospectively included. Serum thyroid ⁃ stimulating hormone （TSH），free thyroxine T4（FT4）and thyroid peroxidase antibody（TPOAb）were measured in early pregnancy. Their clinical data，pregnancy complications and relevant pregnancy outcomes were collected，and the association between TSH levels in early pregnancy and the incidence of HDP was analyzed. Results Among the 2 602 pregnant women，196 developed HDP（incidence rate of 7.53%）. Compared with the non ⁃ HDP group，the HDP group had higher age and body mass index（BMI），higher proportion of assisted reproductive technology（ART）conception，lower gestational weeks at delivery and neonatal birth weight，higher proportion of cesarean section，and higher TSH levels in early pregnancy（P < 0.05）. However，there were no statistically significant difference in FT4 levels and TPOAb positive rate between the two groups（P > 0.05）. The TSH levels in early pregnancy were grouped by quintiles（Q1：0.01-0.60 mIU/L，Q2：0.61-1.11 mIU/L，Q3：1.12-1.63 mIU/L，Q4：1.64-2.43 mIU/L，Q5：2.44-37.44 mIU/L）. The results showed that compared with the Q1 group，the risks of HDP in the Q4group（OR=1.885，95%CI：1.176-3.020，P= 0.008）and the Q5 group（OR=1.755，95%CI：1.088-2.830，P= 0.021）were significantly increased. After controlling potential confounding factors such as the pregnant women’s ages，BMI，ART，FT4 levels and thyroid hormone drug treatment during pregnancy，the risks of HDP in the Q4 group（adjusted OR = 1.856，95%CI：1.108-3.109，P = 0.019）and the Q5 group（adjusted OR=1.910，95%CI：1.106-3.300，P=0.020） were still significantly increased. Conclusion TSH level during early pregnancy > 1.63 mIU/L is an independent risk factor for HDP. Clinicians should pay attention to monitoring blood pressure in pregnant women with high TSH levels.